Sufism Education as a Strategy for Developing Social and Religious Character: A Literature Review of the Book “Mati Sebelum Mati, Buka Kesadaran Hakiki” - Habibi, Mukhlas; Hidayati, Lailatul; Sholihah , Alfiani Rif’atus (Fakultas Tarbiyah dan Ilmu Keguruan UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This article aims to analyzed Sufism education as a strategy for shaping social and religious character in the book Mati Sebelum Mati, Buka Kesadaran Hakiki by Fahruddin Faiz. With a literature review approach, this study examines the concept of Sufism education proposed by the author and its relevance in the context of character formation in society. The method used in this study is a qualitative analysis of the content of the book, identified the basic principles of Sufism that support the development of individual and social character. The results of the study show that Sufism education not only functions as a spiritual tool, but also as an effective strategy in forming a strong social and religious character. Through Sufism practices, indiv iduals can experience profound self-transformation, increasing awareness of moral, ethical, and social values that are important in community life. This article concludes that the application of Sufism education has great potential to build a better character among the younger generation, as well as encourage the creation of a harmonious and civilized society.